Visual C++ 4 unleashed - Toth, Viktor (Sams Pub., 1996)
Written by a team of experts in Visual C++ programming, this is the ultimate reference for Visual C++ programmers. The integration of the text and CD makes this an invaluable tool for accomplished Visual C++ programmers--everything they need to know as well as the tools and utilities to make it work. Includes topics important to developers including File I/O, device control, performance tuning, and more.